Performance of Periparturient Dairy Cows Fed Alfalfa Hay in Total Mixed Ration : A Field Trial in Thailand - Theera Rukkwamsuk,; Sunthorn Rungruang,; Apassara Choothesa,; Theo Wensing, (Agriculture and Natural Resources, 2008)
Performance of 20 periparturient Holstein Friesian dairy cows fed alfalfa hay-base total mixed rations during transition and lactation periods was studied in a commercial dairy farm. From 7 d prior to anticipated calving date until 7 d after calving, all cows were also drenched with 400 ml of propylene glycol once daily. Blood samples were collected at -2, 1, 2, 3 and 4 wk from parturition. Milk yields were recorded daily, and milk samples were collected twice a week to determine milk compositions. Compared with the concentrations at -2 wk, serum glucose and urea nitrogen concentrations decreased whereas serum non-esterified fatty acid and β-hydroxybutyrate concentrations increased after calving. These results indicated that these cows entered some degrees of negative energy balance. Average milk production during 30 d postpartum was 34.8 ± 8.7 kg/d. Average days from calving to first service was 86 ± 24 d, and 55% of 20 cows were conceived at first service. In conclusion, cows fed alfalfa hay-base diet and drenched with propylene glycol during periparturient period could improve negative energy balance, milk yield and conception rate. However, replacing roughages from agro-industry by product with alfalfa hay in Thai dairy farms would depend on the economical analysis because most alfalfa hay was imported from foreign country.